Clinical effects of colesevelam in hispanic subjects with primary hyperlipidemia and prediabetes (2012)
Objective: To evaluate the efficacy and safety of colesevelam in Hispanic subjects with primary hyperlipidemia and prediabetes. Materials and Methods: A 16-week, randomized, double-blind, placebo-controlled, multinational study evaluating colesevelam in participants with primary hyperlipidemia (low-density lipoprotein cholesterol [LDL-C] level > 100 mg/dL) and prediabetes (fasting plasma glucose level > 110 to less than 125 mg/dL, or 2-hour postload glucose level > 140 to less than 200 mg/dL during an oral glucose tolerance test) was conducted between January 14, 2008 and April 3, 2009. Participants were randomized 1:1 to colesevelam 3.75 g/day or placebo. The primary efficacy endpoint was mean change from baseline in LDL-C level with colesevelam compared with placebo. Participants who self-identifed as Hispanic during enrollment were included in this exploratory analysis evaluating the effcacy of colesevelam in Hispanics with primary hyperlipidemia and prediabetes. Results: From a total of 216 subjects with primary hyperlipidemia and prediabetes, 153 Hispanics were included in this post hoc analysis; 77 subjects were randomized to colesevelam and 76 subjects were randomized to placebo. At week 16, LDL-C levels were significantly reduced with colesevelam compared with placebo (mean treatment difference, -19.4%; P less than 0.0001). Achievement of LDL-C level less than 100 mg/dL was more frequent with colesevelam than with placebo (27% vs 11%; P = 0.002). In addition, significant mean reductions in non-high-density lipoprotein cholesterol, total cholesterol, and apolipoprotein B levels (P less than 0.0002 for all), and a significant median increase in triglyceride levels (P = 0.003), were seen with colesevelam compared with placebo. At study end, there was a significant mean reduction in glycated hemoglobin levels and median reduction in fasting plasma glucose levels with colesevelam compared with placebo (P less than 0.02 for both). A fasting plasma glucose level less than 100 mg/dL was achieved in 44% of colesevelam recipients compared with 23% of placebo recipients (P less than 0.05). Overall, colesevelam was well tolerated. Conclusion: Colesevelam may be a treatment option for Hispanic subjects with primary hyperlipidemia and prediabetes, mainly to reduce LDL-C levels, with added beneficial effect on glucose levels. © Postgraduate Medicine.